Political Marketing And Women Candidates In The 2014 Parliamentary Election In The Kingdom Of Bahrain - Al Jawder, Abdulwahab Yusuf Ebrahim A. Aziz (2018)
The 2002 Constitution of Bahrain guarantees electoral rights for men and women. Thus, this political science thesis focuses on the political marketing strategies and tactics used by female candidates to win the 2014 parliamentary election in the Kingdom of Bahrain. The main aims of this study are to investigate political marketing awareness and the behavior of the candidates in the light of Arab- Muslim culture, reflecting on the frameworks adopted, and the electoral orientations characterized by the performance of the female candidates. This qualitative study uses Grounded Theory to develop a theory based on collected data. Data was collected from two sources: in-depth semi-structured interviews and documents. Ten out of 22 female candidates (i.e. 45.45% of the total nominees) were selected as informants with diversity of qualification and experience from each of the four Governorates based on purposive sampling method – three informants won parliamentary seats, three qualified to the second round and four lost the 2014 Parliamentary Elections. This also reflected the informants’ diverse demography and cultures considering the cultural diversity across the Governorates. To maintain validity, the findings were triangulated. To evaluate the informants’ strategies, the study utilizes Strength, Weaknesses, Opportunity and Threats strategy (SWOT). The research findings show that the candidates’ behavior was controlled and influenced by Arab-Muslim culture, notably masculinity, tribalism, stereotype and uncertain avoidance.